Identification of the primary processes that lead to the drop in divertor target ion current at detachment in TCV. Issue 6 (14th February 2018) - Fil, A.; Dudson, B.; Lipschultz, B.; Moulton, D.; Verhaegh, K.; Fevrier, O.; Wensing, M.; ,; ,
Abstract : Using SOLPS‐ITER, we model a TCV conventional divertor discharge density ramp to understand the role of various processes in the loss of target ion current. We find that recombination is not a strong contributor to the rollover of the target ion current at detachment. In contrast, the divertor ion source appears to play a central role in magnitude (the source of most of the ion target current) and time, apparently dropping during the density ramps as a result of a drop in power available for ionization.